The Use of the Problem-Based Learning Model to Improve Students’ Understanding in Islamic Education (PAI) Learning at Vocational High School (SMK) - Wulandari, Atikah; Fatimah, Siti (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to describe students’ understanding before and after the implementation of the Problem Based Learning (PBL) model as well as to identify the challenges and their solutions. The method used was Classroom Action Research (CAR) conducted in two cycles with 32 tenth-grade students of SMK Teknologi Informasi as the subjects. The research instruments consisted of observation sheets for teacher and student activities and comprehension tests administered at the end of each cycle. The results showed that before the implementation of PBL, the students’ average score was only 67.3 with a mastery level of 56.25%. After applying PBL, there was an improvement in cycle I with an average score of 80.3 (87.5% mastery) and in cycle II with an average score of 84 (100% mastery). The challenges encountered were that some students were passive during discussions and there was limited time allocation. The solutions provided included intensive guidance, equal distribution of roles within groups, and more effective time management.